2006
DOI: 10.1161/circulationaha.106.612267
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Completeness of Percutaneous Coronary Intervention Revascularization on Long-Term Outcomes in the Stent Era

Abstract: Background-The importance of completeness of revascularization by percutaneous coronary intervention in patients with multivessel disease is unclear in that there is little information on the impact of incomplete revascularization outside of randomized trials. The objective of this study is to compare long-term mortality and subsequent revascularization for percutaneous coronary intervention patients receiving stents who were completely revascularized (CR) with those who were incompletely revascularized (IR). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
182
4
10

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 291 publications
(209 citation statements)
references
References 26 publications
10
182
4
10
Order By: Relevance
“…Regarding the clinical relevance of angiographic CR, previous studies have shown conflicting results. Some reports in the pre‐DES era showed the clear benefit of angiographic CR rather than IR, and adverse clinical events related to the residual disease after PCI 3, 4, 5, 6, 7, 8. However, other studies reported unclear benefit of angiographic CR over IR 15, 16, 17.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the clinical relevance of angiographic CR, previous studies have shown conflicting results. Some reports in the pre‐DES era showed the clear benefit of angiographic CR rather than IR, and adverse clinical events related to the residual disease after PCI 3, 4, 5, 6, 7, 8. However, other studies reported unclear benefit of angiographic CR over IR 15, 16, 17.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies suggested that angiographic complete revascularization (CR) was more advantageous than incomplete revascularization (IR) and residual disease was associated with adverse clinical outcome after PCI,3, 4, 5, 6, 7, 8 the evidence regarding the benefit of angiographic CR over IR has been limited in CKD patients with multivessel CAD. Given the increasing prevalence of CKD, it would be an important issue to clarify the safety and efficacy of angiographic CR in this high‐risk population 1, 9.…”
mentioning
confidence: 99%
“…Observational studies suggest that a successfully revascularized CTO confers a significant 5-and 10-year survival advantage compared with failed revascularization. A New York State survey showed that incomplete revascularization by PCI leaving untreated CTOs led to higher 3-year mortality [199]. Thus, similar to non-chronically occluded vessels, revascularization of CTO may be considered in the presence of angina or ischaemia S32 Rotablation is recommended for preparation of heavily calcified or severely fibrotic lesions that cannot be crossed by a balloon or adequately dilated before planned stenting.…”
Section: Specific Lesion Subsetsmentioning
confidence: 99%
“…Summary-The importance of complete revascularization among patients with stable multi-vessel coronary artery disease (CAD) is uncertain based on data from registries [24][25][26] and trials. [27][28][29][30] The authors performed a post-hoc analysis to determine the effect of complete revascularization on 10-year survival of patients with stable multi-vessel CAD and preserved left ventricular ejection fraction (EF) who were randomly assigned to percutaneous coronary intervention (PCI) or coronary artery bypass graft (CABG) in the Second Medicine, Angioplasty, or Surgery Study (MASS II) Trial.…”
Section: Effect Of Complete Revascularization On 10-year Survival Of mentioning
confidence: 99%